GENDER AND FEMINISM IN THE DAILY NEWSPAPER PEKANBARU METRO EXPRES (MX): A Study of Critical Discourse Analysis from Sara Mills' Perspective - Dwi Viora (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The news about women in some newspapers, still dominated news of violence against women. Gender inequality is also often seen in positioning actors in the Daily Newspaper. Women are always an object in the news and its presence is always displayed by others. The purpose of this research is (1) to describe the position of actor in Pekanbaru Metro Expres Daily (MX), (2) to describe reader position in Pekanbaru Metro Expres (MX) Daily Newspaper. This research type is qualitative research with descriptive method. This study uses instrument in the form of documentation. The results of this study were (1) the victimized woman only as an object in the news, while the perpetrator and the police became the subject who told the chronology of the event, (2) the reader would position himself as a man because the news was written based on information obtained from the perpetrator and Police. Therefore, it can be concluded (1) there has been no concern for gender and feminism, (2) the reader positions itself as a man because the news only tells about the perpetrator.